Business Comparative Analysis on Kopi Jigana Business and Kopi Inspirasi - Arina Nur Farida (Diversity: Jurnal Ilmiah Pascasarjana, 2023)
Coffee is one of the plantation commodities that has an important role in the Indonesian economy. The proliferation of coffee shops has led to intense business competition, resulting in fluctuations in sales for coffee shops that are less able to compete. This study aims to describe the characteristics of consumers, business processes, as well as the potential and constraints experienced by Lain Hati coffee and Kedai Kopi Inspiration. The method used in this study is a survey method with descriptive statistical analysis tools. The number of samples in this study were 15 people on Jigana coffee and 15 people on Inspiration Coffee. The results showed that the characteristics of consumers in Jigana coffee and Kopi Inspirasi were dominated by men and of productive age, from 20-30 years old with an average income of Rp. 1,000,000 - Rp. 5,000,000. In terms of consumer behavior, most of the consumers of the two coffee shops are more interested in coffee that tastes good/delicious and has a comfortable atmosphere. The business processes in Jigana coffee and Inspiration coffee are relatively the same. The potential and constraints of Jigana coffee and Inspiration coffee are in product variables, location, facilities, equipment completeness, and human resources.